Pelatihan Membatik Bagi Pengembangan Jiwa Creativepreneur Santriwati Pondok Pesantren Nur Muhammad Landungsari - Pujiyanto, Pujiyanto; Ratnawati, Ika; Hidajat, Robby; Hasiymy, Muhammad Affaf (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This training program aims to develop the spirit of createvepreneur, and  cultural potential among santriwati in the art of batik at Nur Muhammad Landungsari Islamic Boarding Scholl, Karangploso District, Malang Regency, East Java. This program was carried out through training and evaluating of batik training for 40 santriwati’s. The training began with a welcome speech and continued with a basic presentation of batik making. The desired achievement is an increase in knowledge about batik and mastery of the basic skills of batik. Based on survey results, there is high enthusiasm and trust in social media adapting of batik motifs. The prospects for developing batik skills among santriwati’s are very promising and open up opportunities for creative entrepreneurship. Batik skills are part of a Muslim woman’s unique identity and show pride in local culture. By developing a curriculum that integrates entrepreneurship and the art of batik, santriwati’s are able to become a generation that has an entrepreneurial spirit and can develop cultural potential as part of their identity and at the same time their economic independence. The outputs of this training programs is to create unique products with high selling value and promote Indonesia culture and can have a positive impact on santriwati and the community at Nur Muhammad Landungsari Islamic Boarding Scholl.